THE DETERMINANTS OF PURCHASING DECISIONS - Melati; Rahayu Lestari; Suadi Sapta Putra; Kumba Digdowiseiso; Khatijah Omar (PT. Radja Intercontinental Publishing, 2024)
The objective of this study is to ascertain the primary factors that impact consumer buying choices within the realm of online food delivery services. The research focuses on analyzing various factors, including trust, convenience, materialism, novelty seeking behavior, product visibility, positive online reviews, and frequency of use, as the primary determining variables. The employed approach entails conducting a Systematic Literature Review (SLR) to gather, assess, and integrate the findings of prior research. The research findings indicate that the combination of trust and convenience has a substantial influence on consumer buying choices. In addition, the intensity of purchase intentions is also influenced by materialism factors and novelty-seeking behavior. The presence of product visibility and favorable online reviews seems to moderate the connection between these factors and the intention to make a purchase. The presence of this regulating factor emphasizes the significance of product visual elements and customer testimonials in shaping purchasing choices. These findings offer profound understanding of the intricate dynamics involved in consumers' decision-making process when using online food delivery services. Theoretical implications highlight the significance of these determining variables, while practical implications offer guidance for service providers and restaurants to enhance marketing strategies and customer experience in order to bolster purchase intentions. This study significantly enhances our comprehension of the determinants that impact purchasing choices in the expanding age of online food delivery services.